2012
DOI: 10.1111/j.1365-3091.2012.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a transgressive barrier within a regressive strandplain system: Implications for complex coastal response to environmental change

Abstract: Clastic, depositional strandplain systems have the potential to record changes in the primary drivers of coastal evolution: climate, sea‐level, and the frequency of major meteorological and oceanographic events. This study seeks to use one such record from a southern Brazilian strandplain to highlight the potentially‐complex nature of coastal sedimentological response to small changes in these drivers. Following a 2 to 4 m highstand at ca 5·8 ka in southern Brazil, falling sea‐level reworked shelf sediment ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 102 publications
(251 reference statements)
6
99
1
6
Order By: Relevance
“…The clayey and silty sands are mostly found at south from Pinheira in small bays and lowlands around the estuarine and lagoon systems. In Pinheira strandplain, the Holocene terrace clearly corresponds to a strandplain, as evidenced by the sets of foredune ridges (Hesp et al 2009, Barboza et al 2009, Dillenburg et al 2014, Hein et al 2014.…”
Section: Geologic and Geomorphologic Featuresmentioning
confidence: 99%
“…The clayey and silty sands are mostly found at south from Pinheira in small bays and lowlands around the estuarine and lagoon systems. In Pinheira strandplain, the Holocene terrace clearly corresponds to a strandplain, as evidenced by the sets of foredune ridges (Hesp et al 2009, Barboza et al 2009, Dillenburg et al 2014, Hein et al 2014.…”
Section: Geologic and Geomorphologic Featuresmentioning
confidence: 99%
“…Destacam-se os trabalhos de Barboza et al (2009Barboza et al ( , 2014a, Fornari (2010), Tanaka (2010), Biancini da Silva (2011, 2016 Biancini da , Dillenburg et al (2011, Hein et al (2013), , e Leal et al (2016).…”
Section: Introductionunclassified
“…More recently, the eustatic sea-level rise following the last glacial maximum resulted in a highstand approximately 5.8 ka ago, encroaching in some locations upon Pleistocene highstand barriers (HORN FILHO et al, 1997;CARUSO JR et al, 2000, DOMINGUEZ, 2009). Since then the sea level has fallen 2 to 4 m (SUGUIU et al, 1985;LESSA, 1997;ANGULO et al, 2006;HESP et al, 2009;MCBRIDE et al, 2013;HEIN et al, 2013HEIN et al, , 2014 as a consequence of global isostasy, as demonstrated by MITROVICA and MILNE (2002).…”
Section: Study Areamentioning
confidence: 99%
“…This part of the coast is characterized by the high relief of the nearby Serra do Mar range, with a series of grabens and horsts parallel to the current coastline that were created by the Tertiary collapse (58 M yr BP) of a large Cretaceous plateau (ZALÁN; OLIVEIRA, 2005), giving rise, over the course of 30 million years, to Large-scale sea-level fluctuations throughout the Quaternary resulted in the deposition of a series of transgressive barriers and regressive barrier-strandplain systems, thus straightening the bedrock-dominated shoreline (DOMINGUEZ, 2009;KLEIN et al, 2010;MCBRIDE et al, 2013;HEIN et al 2013HEIN et al , 2014. Two Quaternary barriers, dating from the Oxygen Isotopic Stage (OIS) 5e and mid-Holocene highstands (SUGUIO et al, 1985;VILLWOCK et al, 1986;MARTINS et al, 1988) have been identified on the central coast of Santa Catarina where the Serra do Mar mountain range abuts the modern coast (HORN FILHO et al, 1997;CARUSO JR et al, 2000;MCBRIDE et al, 2013;HESP et al, 2009;HEIN et al, 2013HEIN et al, , 2014.…”
Section: Study Areamentioning
confidence: 99%